Mental healthcare-seeking behavior during the perinatal period among women in rural Bangladesh - Goutam Kumar Dutta; Bidhan Krishna Sarker; Helal Uddin Ahmed; Dipika Shankar Bhattacharyya; Md. Musfikur Rahman; Ratna Majumder; Taposh Kumar Biswas (BMC, 2022)
Abstract Introduction Mental health conditions are of rising concern due to their increased contribution to the global burden of disease. Mental health issues are inextricably linked with other socio-cultural and health dimensions, especially in the rural areas in developing countries. The complex relationship between mental health issues and socio-cultural settings may largely toll upon healthcare-seeking behavior. So, it urges to document the current status of mental healthcare-seeking behavior during the perinatal period among rural women in Bangladesh to develop a context-specific intervention in the future. Methods This study was carried out in one sub-district in Bangladesh from April 2017 to June 2018. We conducted 21 In-depth Interviews (IDIs) and seven Focus Group Discussions (FGDs) with different groups of purposively selected participants. After collecting the recorded interview and making the verbatim transcription, the data were coded through Atlasti 5.7.a. Data were analyzed thematically to interpret the findings. Results Two-thirds of the total respondents did not seek mental healthcare during the perinatal period at the community level. They also did not know about the mental health service provider or the facility to get set these services. Only one respondent out of twenty-one sought maternal mental healthcare from a gynecologist from a private hospital. Socio-cultural factors such as social stigma, traditional beliefs and practices, social and religious taboos, and social capital negatively influence healthcare-seeking behaviors. Besides, the community-level service providers were not found to be adequately trained and did not have proper guidelines regarding its management. Conclusion The findings provide evidence that there is an urgent need to increase the awareness for service users and formulate a guideline for the community-level service provider to manage maternal mental problems during the perinatal period of women in rural Bangladesh.